2011
DOI: 10.1007/s10882-011-9260-2
|View full text |Cite
|
Sign up to set email alerts
|

Social Skills Differences Between the Autism Spectrum Disorders

Abstract: Social skills deficits are one of the core features of autism spectrum disorders (ASDs), with many believing that this symptom domain is the defining feature of individuals with ASDs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
3
0
1
Order By: Relevance
“…For example, friends can provide emotional support to adolescents during difficult times and serve as a buffer against peer victimization and exclusion (Kenny et al 2013). Because of their social skills deficits, individuals with ASD, particularly adolescents with ASD, are at risk for a host of negative outcomes such as peer rejection and internalizing problems (Kozlowski et al 2012). …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, friends can provide emotional support to adolescents during difficult times and serve as a buffer against peer victimization and exclusion (Kenny et al 2013). Because of their social skills deficits, individuals with ASD, particularly adolescents with ASD, are at risk for a host of negative outcomes such as peer rejection and internalizing problems (Kozlowski et al 2012). …”
Section: Introductionmentioning
confidence: 99%
“…Given that poor social functioning is a hallmark feature of ASD (Kozlowski et al 2012), developing and testing the efficacy of social skills interventions for individuals with ASD is critical. While some social skills interventions have been proven to be efficacious in research settings using resource-intensive randomized controlled trials (RCTs), it is unclear whether the gains observed in these trials will generalize to routine community-based practice (Dingfelder and Mandell 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Además del funcionamiento social deteriorado, los jóvenes con TEA de alto funcionamiento a menudo presentan ansiedad comórbida, pudiendo tener una mejor comprensión de sus anomalías de comportamiento, lo que puede hacer que sean vulnerables a experimentar altos niveles de ansiedad (Hallett et al, 2013). Debido a sus deficiencias en las habilidades sociales, las personas con TEA, sobre todo las que se encuentran en edad adolescente, corren el riesgo de sufrir el rechazo de los compañeros y problemas de internalización (Kozlowski et al, 2012).…”
Section: Introductionunclassified
“…The second requires complex social dynamics as witnessed during free play and often controlled by peers in the playground (Walker et al, 1998 ). The first of these demands is essential in creating an environment in which learning can take place, while the second is imperative in preventing disassociation from the school system (Bellini, 2006 ; Bellini & Akullian, 2007 ; Kozlowski et al, 2012 ; Tantam, 2000 ).…”
Section: Introductionmentioning
confidence: 99%